Estrategia de comunicación digital y producción de contenidos para la marca de ropa Baby Lemonade - Olórtegui Taramona, Alejandra (2020)
The following project, done in october of 2018, presents the planning and realization of the digital communication strategy and content production for the second-hand vintage clothing brand Baby Lemonade. Two stages of the campaign were proposed and the contents for both stages were produced, including two photographic sessions, but due to the client's personal issues, she decided to put the project on standby so the second part of the project was suspended. This document will present the contents of our complete proposal: first and second part of the campaign. This strategy seeks to differentiate the brand from similar proposals to the rest of the market, exploiting its purpose of creating awareness in the user by encouraging them to give different pieces of clothing a second chance and avoiding the excessive consumerism that the fashion industry entails. Prior to our project, the brand did not have a communication strategy nor had an analysis of the brand's behavior on social media. Likewise, there was a lack of consistency and quality in the content nor did they have a defined visual proposal, so one of the most significant changes that can be seen from the first stage of the project is an improvement in that area. This campaign sought to generate a greater reach of the brand towards its target audience through investment in social networks, as well as generate engagement with its followers. The results of the campaign were measured based on our digital objectives, prioritizing those that performed better versus those that performed worst. This was reflected by the increase in sales of the garments that were distributed on Baby Lemonade's Facebook and Instagram page.